2005
DOI: 10.1111/j.1365-2443.2005.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Aurora C is directly associated with Survivin and required for cytokinesis

Abstract: Much recent attention has been focused on Aurora C, the third member of the mammalian Aurora kinases family that plays significant roles in mitosis. We report here that using sensitive RT-PCR to amplify the C-terminal, we found that Aurora C is not only expressed highly in testis, but also among 16 other human tissues in a broad-spectrum way. Aurora C, as a chromosomal passenger protein, is co-localized with Aurora B and Survivin in mitotic cells. Aurora C can also be associated with Aurora B and Survivin in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
90
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 33 publications
8
90
0
3
Order By: Relevance
“…Recently, it has been demonstrated that Aurora-C is a new member of the chromosomal passenger proteins interacting, similarly to Aurora-B, with INCENP and survivin, thus contributing to the regulation of chromosome segregation and cytokinesis 22,41 . In this context, it is worthwhile to mention that Aurora-B and C share the highest degree of sequence overlap with about 83% sequence identity whereas the kinases C and A share about 71% sequence identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that Aurora-C is a new member of the chromosomal passenger proteins interacting, similarly to Aurora-B, with INCENP and survivin, thus contributing to the regulation of chromosome segregation and cytokinesis 22,41 . In this context, it is worthwhile to mention that Aurora-B and C share the highest degree of sequence overlap with about 83% sequence identity whereas the kinases C and A share about 71% sequence identity.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 Recently, also the Aurora kinase C has been demonstrated to be a chromosomal passenger protein, colocalized and able to form a complex with Aurora-B, INCENP and survivin in mitotic cells. 22 The genes encoding the 3 Aurora kinases map into regions that are affected by chromosomal abnormalities in different cancer types, and their overexpression has been detected in several tumor cell lines. 23 Aurora-A gene lies within the human chromosome region 20q13, and it is amplified in many forms of cancer such as bladder, ovarian and, at high frequency, in colorectal tumors.…”
mentioning
confidence: 99%
“…Therefore, our findings provide new insight into the role of AURKA in regulating p53-dependent apoptosis and enrich existing knowledge of AURKA and p53, as previous reports have shown that AURKA regulates p53 protein levels through direct interaction and phosphorylation of p53 at phosphorylation at Ser315 17 and Ser215. 34 The p53 protein is a major regulator of apoptosis, and several cancer drugs work through induction of DNA damage and activation of p53-mediated apoptosis. 35,36 The biological outcome of p53 depends on its ability to activate its downstream proapoptotic transcription targets.…”
Section: Discussionmentioning
confidence: 99%
“…The encoded protein AURKC is a member of the cell cycle regulatory serine/threonine kinases (AURK A, B and C) which are essential during the mitotic cell division. AURKC is expressed specifically in the testis [14,23] where it is involved in chromatin condensation and proper attachment of homologous chromosomes during the first meiotic division [24,16]. The two recurrent truncating mutations, frameshift c.144delC mutation and p.Y248*, are expected to have a severe impact on the protein function.…”
Section: Discussionmentioning
confidence: 99%
“…AURKC protein is the third member of the Aurora subfamily of serine/threonine protein kinases and is preferentially expressed in the testis [14][15][16]. It was demonstrated that AURKC participates in the control of microtubule-kinetochore attachment, verifying the bi-orientation of the tensions preceding chromosome segregation, thus ensuring the production of euploid gametes.…”
Section: Introductionmentioning
confidence: 99%